Genetic analysis of yield and its components traits in rice (Oryza sativa L.) - Patel Shashikant Kacharabhai (Electronic Journal of Plant Breeding, 2015)
The nature of gene interaction in the inheritance of 12 yield and its components traits was studied deploying generation mean analysis following 5 parameter model for parents, F1, F2, and F3generations of four crosses of rice. The results indicated that gene action differs over crosses. In general, most of the traits are governed by non- additive gene action.